2015
DOI: 10.1021/acssuschemeng.5b00036
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Properties of Activated Carbons Prepared from Waste CDs and DVDs

Abstract: Two sets of activated carbons have been prepared from waste CDs and DVDs by carbonization and subsequent activation with either KOH or CO 2 . The resulting activated carbons had specific surface area in the range of 500− 2240 m 2 g −1 , total pore volume in the range of 0.18−1.36 cm 3 g −1 , volume of micropores and small mesopores (w < ∼2.9 nm) in the range of 0.17−1.25 cm 3 g −1 , and volume of small micropores (w < ∼1.2 nm) in the range of 0.14−0.71 cm 3 g −1 . Both KOH and CO 2 activation resulted in 5−45-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(28 citation statements)
references
References 31 publications
1
27
0
Order By: Relevance
“…The CO 2 uptake of Agar-0.5-600-1 at 298 K (3.7 mmol g À 1 ) is lower than some of the reported results, however the uptake of 6.5 mmol g À 1 at 273 K is still very competitive when compared with other carbon materials. For instance, nitrogen doped C-KOH-4 prepared from wasted CDs and DVDs by Jaroniec et al showed a high S BET of 2240 m 2 g À 1 , but the CO 2 uptake at 273 K was 5.8 mmol g À 1 , the lower uptake could be attributed to the generation of abundant mesopores under harsh activation conditions; [19] carbon material KBM-700 with MOF as the carbon and nitrogen source had a high nitrogen content of 10.16 wt %, the low CO 2 uptake of 4.75 mmol g À 1 was due to the fact that the microporosity in KBM-700 was greatly contributed by micropores larger than 1 nm. [6a] The adsorption isotherms of Agar-0.5-550-1 and Agar-0.5-600-1 are very close, but an obvious deterioration of CO 2 uptake is witnessed when the activation temperature reaches 650 or 700°C.…”
Section: Resultsmentioning
confidence: 99%
“…The CO 2 uptake of Agar-0.5-600-1 at 298 K (3.7 mmol g À 1 ) is lower than some of the reported results, however the uptake of 6.5 mmol g À 1 at 273 K is still very competitive when compared with other carbon materials. For instance, nitrogen doped C-KOH-4 prepared from wasted CDs and DVDs by Jaroniec et al showed a high S BET of 2240 m 2 g À 1 , but the CO 2 uptake at 273 K was 5.8 mmol g À 1 , the lower uptake could be attributed to the generation of abundant mesopores under harsh activation conditions; [19] carbon material KBM-700 with MOF as the carbon and nitrogen source had a high nitrogen content of 10.16 wt %, the low CO 2 uptake of 4.75 mmol g À 1 was due to the fact that the microporosity in KBM-700 was greatly contributed by micropores larger than 1 nm. [6a] The adsorption isotherms of Agar-0.5-550-1 and Agar-0.5-600-1 are very close, but an obvious deterioration of CO 2 uptake is witnessed when the activation temperature reaches 650 or 700°C.…”
Section: Resultsmentioning
confidence: 99%
“…-Synthesis of a new sorbent using compounds with polar moieties. In this way, silica-based materials: RP-cyano, RP-hydroxyl, RP-amine [43], polar polymers [2,21,[25][26][27][28] and chemically activated or porous carbons [21,[27][28][29]39] can be produced.…”
Section: The Way Of Interaction With Sorbentsmentioning
confidence: 99%
“…To create abundant micropores, pristine carbons are usually subjected to post-synthesis activation. KOH [15][16][17][18] is the most frequently used activation agent, while K 2 CO 3 [19], H 3 PO 4 [20], ZnCl 2 [21], NH 3 [22,23], CO 2 [24,25], and H 2 O [26,27] have been less frequently employed. Jaroniec et al [28] compared the ability of different agents for the activation of a commercial carbon and found KOH-activated carbon had the most developed microporosity and enhanced adsorption capacity for CO 2 .…”
Section: Introductionmentioning
confidence: 99%